Semilobar Holoprosencephaly Seen with Diffusion Tensor Imaging and Fiber Tracking - Rollins, Nancy (American Journal of Neuroradiology, 2005)
Summary: A neonate with semilobar holoprosencephaly was studied with diffusion tensor imaging and fiber tracking. Fiber tracking showed that the frontooccipital fasciculi were in continuity across the ventral midline, interposed between fused caudate and dysplastic fornices. Tractography of the posterior limbs of the internal capsules showed fibers arching ventrally toward the expected location of the motor cortex; some fibers also coursed dorsally, presumably to the sensory cortex. There was a posterior commissural white matter bundle representing a callosal splenium. Diffusion tensor imaging and fiber tracking revealed white matter structures not apparent on routine imaging sequences, which are in agreement with pathologic descriptions of the holoprosencephalic brain.